Women and sexuality. Querétaro, (México) 1940-1960 (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The research seeks to explain the discursive and empirical transformations experienced by local women from urban middle class between the years 1940-1960, a period considered as the beginning of the modernization process, from those proposed in the women History and gender perspective and also the History of the everyday life. In this context, the reaction of some institutions (church, family, schools, etc.) was adverse to the modernization, because they claimed that inserting women in areas “that are not theirs” would be the beginning of the social chaos. Thus, we will show which were the discourses put forward by the institutions to keep the tradition and what was the State discourse to encourage modernization. It also intends to show how the change impacted on women daily lives, mainly in their sexuality.
Keywords: Women; Querétaro; tradition; modernization; sexuality; education.